Penerapan Model Pembelajaran Problem Based Learning (PBL) Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Biologi Kelas X di SMK Manbaul Hikmah - Istikomah; Alibasyah, Lestari M.P; Buntu, Amalia; Agni, Raya; Rauf, Abd.; Jamhari, Mohammad (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to improve students’ learning outcomes in Biology for Grade X students of SMK Manbaul Hikmah through the implementation of the Problem Based Learning (PBL) model. The research employed a descriptive qualitative approach using a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. Data were collected through observation sheets of teacher and student activities as well as learning outcome tests administered at the end of each cycle. The results indicate that the application of the PBL model significantly improved students’ learning outcomes. In Cycle I, classical learning mastery reached 85%, while in Cycle II it increased to 92%. The 7% improvement in classical mastery demonstrates that the PBL model is effective in encouraging students to think critically, collaborate, and solve problems related to contextual learning materials. In addition, students’ activity and engagement during the learning process showed continuous improvement in each cycle. Therefore, the Problem Based Learning model can be considered an effective alternative for improving Biology learning outcomes of Grade X students at SMK Manbaul Hikmah.